Political parties: extent and nature - Asayesh, Hossein; Ab. Halim, Adlina; Shojaei, Seyedeh Nosrat (Marsland Press, 2011)
The political party is a means of connecting the political process with society and it helps to improve the political system. In addition, a central feature of any democracy is political party which serve as a vehicle through which citizens can come together freely to define their political and policy aspirations and campaign for public office. In fact political parties have developed alongside democracy, and it is commonly assumed that democracy cannot survive without them. This article is an overview from the extent and nature of the political party in any society.